Attracting Foreign Investments in Europe - are Italian Regions Doomed? - Roberto Basile; Luigi Benfratello; Davide Castellani (European Regional Science Association (ERSA), 2005)
Foreign direct investments in Europe have grown substantially over the last decade, but Italian regions account for a very small portion of such increase. Why does Italian regions attract such a low number of foreign investors? Is it a regional or a country problem? One explanation for this pattern could be that the characteristics of Italian regions are not attractive to foreign multinationals. A different, although not alternative, explanation is that Italian regions may be 'doomed' by the fact that they all share common national policies and institutions (such as, tax regimes, efficiency of bureaucracy, degree of labour market regulation and effectiveness of the legal and property right protection system) which discourage foreign firms to locate their plants in Italy. This view follows a tradition of cross-country studies which have addressed the role of institutional and policy characteristics as determinants of inward FDIs. In this paper we will model the potential attractiveness of 52 NUTS1 regions in 5 EU countries in terms of their main observable characteristics and will investigate whether Italian regions attract more or less than their potential. In other words, we will ask whether a EU region with the same characteristics of an Italian region will attract a different amount of FDIs. Second, we will evaluate the impact of some national policy and institutional characteristics on the attractiveness of regions and we will assess the role of such factors in explaining the Italian specificity. Third, we will simulate the relative contribution to FDIs in Italian regions of regional and national variables. This exercise will help us assessing to what extent the low attractiveness of Italian regions is the result of specific regional characteristics or of countrywide factors.
Keywords: 330